The Driving Forces of Economic Growth Before and After the 2008 Global Financial Crisis - Cong, Phan The; Lich, Hoang Khac (International Journal of Economics and Financial Issues, 2017)
This paper investigates the determinants of economic growth in two different periods, 2002-2008 and 2008-2013. As national output can be determined by the functions of production and consumption, the explanatory variables consist of growth rates of investment, labor, household consumption, government spending and exports. Analyzing the data of 129 countries, this paper has four main findings: (i) Investment and exports have positive impacts on economic growth; (ii) Labor has significant positive impact if we investigate the period from 2002 to 2013 as a whole. The effect is only positive in the first period with low statistically significance while remains unclear in the second period; (iii) Household consumption has ambiguous impact on economic growth. There exists some evidences (with 90% confidence level) that household consumption might produce a minor adverse effect on economic growth; (iv) The relationship between economic growth and government spending is positive in the first period and negative in the second. Keywords: Determinants of economic growth, global financial crisis, public expenditure, JEL Classifications: GO1, H5, O4